Long‐term carbon storage through retention of dissolved aromatic acids by reactive particles in soil - Marc G. Kramer; Jonathan Sanderman; Oliver A. Chadwick; Jon Chorover; Peter M. Vitousek (Global Change Biology, 2012)
Soils retain large quantities of carbon, thereby slowing its return to the atmosphere. The mechanisms governing organic carbon sequestration in soil remain poorly understood, yet are integral to understanding soil‐climate feedbacks. We evaluated the biochemistry of dissolved and solid organic carbon in potential source and sink horizons across a chronosequence of volcanic soils in Hawai'i. The soils are derived from similar basaltic parent material on gently sloping volcanic shield surfaces, support the same vegetation assemblage, and yet exhibit strong shifts in soil mineralogy and soil carbon content as a function of volcanic substrate age. Solid‐state 13 carbon nuclear magnetic resonance spectra indicate that the most persistent mineral‐bound carbon is comprised of partially oxidized aromatic compounds with strong chemical resemblance to dissolved organic matter derived from plant litter. A molecular mixing model indicates that protein, lipid, carbohydrate, and char content decreased whereas oxidized lignin and carboxyl/carbonyl content increased with increasing short‐range order mineral content. When solutions rich in dissolved organic matter were passed through Bw‐horizon mineral cores, aromatic compounds were preferentially sorbed with the greatest retention occurring in horizons containing the greatest amount of short‐range ordered minerals. These minerals are reactive metastable nanocrystals that are most common in volcanic soils, but exist in smaller amounts in nearly all major soil classes. Our results indicate that long‐term carbon storage in short‐range ordered minerals occurs via chemical retention with dissolved aromatic acids derived from plant litter and carried along preferential flow‐paths to deeper B horizons.